TRIAZOLOTHIADIAZOLES DRIVED FROM IBUPROFEN AND THIOCARBOHYDRAZIDE: Synthesis, Characterization, docking studies, and Preliminary Pharmacological assessment (Journal of Pharmaceutical Negative Results, 2022)
The synthesis of new NSAIDs with improved efficacy and selectivity towards COX2, which encouraged by 1,2,4-triazoles and 1,3,4-thiadiazoles with their various biological activities. In this experiment, the production of 1,2,4-triazolothiadiazoles derivatives from Ibuprofen. We have enhanced anti-inflammatory and analgesic activities by conventional method and microwave-assisted technique, and then compare the time consuming by reaction and yield percent of the product in both way, besides anti-inflammatory activity evaluation of targeted compounds by pharmacological test with predictable selectivity towards COX-2 enzyme. A successful synthesis of the target compounds has been achieved by checking purity, characterization, also identification of the synthetic compounds which detected by estimation of physical properties, FT-IR and ¹H-NMR spectroscopy. The anti-inflammatory properties of the ending compounds in vivo are being evaluated using egg-white-induced edema models. The experienced compounds (1 MIC., 1 CON.) and the reference drug (Ibuprofen) produced significant reduction in paw edema in compare to the effect of control group. Wholly tested compounds produced considerable decrease of paw edema in contrast to control group. However, final synthesis compounds have considerable more paw edema declining than Ibuprofen. Intermediate and target compounds are synthesis by microwave method have better result by time, purity and yield in compare with conventional way. The synthesized compounds (1 or 2 or 3 MIC.,1 or 2 or 3 or CON.) may exhibit expected selectivity towards COX-2 enzyme properly due to their large size than its parent Ibuprofen.